Damping device to reduce the risk of injection-coupled combustion instabilities in liquid propellant rocket engines. (April 2020) - Armbruster, Wolfgang; Hardi, Justin S.; Miene, Yannik; Suslov, Dmitry; Oschwald, Michael
Abstract: A new countermeasure against injection-coupled combustion instabilities in liquid propellant rocket engines is presented. Whereas the problem is usually addressed by adding damping elements such as baffles or resonators to the combustion chamber, this approach directly damps the acoustic eigenmodes of the injector instead. The principle of the damping method is described in this article, as well as the implementation of such a device in a sub-scale rocket thrust chamber operated with liquid oxygen and hydrogen at conditions representative of upper stage engines. Test results are presented which show that flame and pressure oscillations were successfully reduced by the modification. The absorbers had no measurable influence on thrust chamber performance, and so the solution lends itself to retrofitting in existing engines, as well as integration during the design phase. Highlights: New damping device for high-frequency combustion instability designed and tested. Dampers are connected to injectors instead of combustion chamber. Once sufficiently tuned, the resonators work for all operating conditions. Injector-driven combustion instability was drastically reduced by the device. The damping device had no negative effect on injector performance.